(untitled) (Clinics, 2021)
OBJECTIVES: Demonstrate that continuous peripheral nerve block (CPNB) may be an alternative with adequate analgesia and a lower incidence of side effects for ischemic pain due peripheral obstructive arterial disease (POAD). METHODS: Retrospective cohort study with 21 patients with POAD, Fontaine IV graded, with foot pain. Patients were submitted to continuous sciatic nerve block (CSNB), through a perineural catheter. Primary outcomes were pain intensity (by numerical rating scale) and opioid consumption (in oral morphine equivalents). RESULTS: During CSNB, pain scores markedly decreased in comparison to the pre-block period. CONCLUSIONS: CPNB may be a good option for ischemic pain treatment in in-patients, as it provides effective pain control with fewer adverse effects.